Preserving the human moment (In memoriam Francisco Javier Pe\~nas) - Stefano Guzzini (Danish Institute for International Studies (DIIS), 2019)
In early 2018 Francisco Javier Pe\~nas Esteban, Paco for his friends, unexpectedly died in Argentina. Prof. Pe\~nas has been a major force for institutionalising the IR theory (International Relations) in Spain. Working at the Universidad Autónoma de Madrid, and against many odds and resistance, he established a small but energetic 'Grupo de Estudios de Relaciones Internacionales' and launched the journal 'Relaciones Internacionales', online and open access. Frank, and sometimes caustic in style, he inspired many students and collaborators for the need to theorise international affairs' and not to stay content with the common sense or the 'idées reçues', be they driven by mere good intentions or all-too-facile (and sterile) cynicism. In view of honouring and pursueing his legacy, the journal 'Relaciones Internacionales' organised a special issue engaging Prof. Pe\~nas' work in early 2019. Stefano Guzzini contributed with an article that revisited Pe\~nas' style and content of theorising International Relations. This DIIS Working Paper is the English version of the article published in Spanish.
Keywords: 330